ผู้หญิงอินเดีย: สัญญะ การสร้างความหมาย และการตอบโต้มายาคติ ในนิยายเบงคลีของเสฐียรโกเศศ-นาคะประทีป - พิมพ์วิภา พินิจ (คณะมนุษยศาสตร์ มหาวิทยาลัยเกษตรศาสตร์, 2022)
This article aims to study cultural signs about women and signification in three tales named Kontokon (His Trick, Her Trick), Thepthida Itu (The Goddess Itu), and Songjaobaw (The Two Grooms) from Sathirakoses-Nagapradipa’s Niyai Bengali, translated from Bengali Household Tales. The framework applied to this research is the framework of Roland Barthes’s Semiology. The result displays that the tales convey three significant signs which are (1) the brahmin women, signifying that women are brave and able to defeat men by using their wit. Besides women do not have to be under guardianship of men or conform to social norms, (2) The ritual of Itu points out the importance and power of relationships among sisterhood and female community, which can make a change without man’s assistance, and (3) Vikramaditya and princess’s rings convey gender equality and bravery of women to stand up for justice and themselves. The roles of these signs are to criticize and counter against a myth of patriarchy in Indian society.